Pengaruh Kepuasan Kerja, work life balance terhadap kinerja yang dimoderasi oleh flexible working arrangement pada PT Bina Artha Ventura 3 Makassar - Nur Sri Wahyuni; Idayanti Nursyamsi; Andi Reni (Scientium Management Review, 2023)
This examine objectives to determine the reaction of working ladies to the implementation of do business from home as a shape of adaptation during the pandemic at PT. Bina Artha Ventura, knowing the impact of work from home, job pride, and work life balance on the overall performance of lady employees at PT. Bina Artha Ventura throughout the Covid 19 pandemic duration and knowing the impact of the work from home variable as a moderator on the connection between activity satisfaction and paintings existence balance on performance among girl people at PT. Bina Artha Ventura in the course of the Covid 19 pandemic length. The facts used consisted of primary and secondary facts and changed into analyzed qualitatively and quantitatively. The results confirmed that PT. Bina Artha Ventura had made adaptations to running hours earlier than, all through and after the Covid-19 pandemic but this edition method acquired a poor reaction from operating girls due to excessive working hours and running days at some point of the post-pandemic duration. The results of multiple linear regression analysis show that job satisfaction, work life balance, and flexible working arrangements have a positive and partially significant effect on the performance of female workers at PT. Bina Artha Ventura during the Covid-19 pandemic period. The results of the moderation regression analysis show that the Flexible Working Arrangement is able to moderate the relationship between Work Life Balance and Performance in female workers at PT Bina Artha Ventura during the Covid-19 pandemic period but does not significantly moderate Job Satisfaction with Performance.